Development of Local History-Based Teaching Materials at SMA Negeri Semadam, Aceh Tenggara Regency - *Syahrul Aprianda; Ramazan Ramazan; Bukhari Bukhari (Universitas Syiah Kuala, 2022)
The purpose of this study is to find out how the development and feasibility of teaching materials based on the local history of the Alas people's struggle against the Dutch colonialism in the material of Aceh jihad class XI IPS SMA Negeri Semadam, Southeast Aceh Regency. This type of research is a type of development research using a qualitative descriptive approach. The results of the research were in the form of developing teaching materials based on the local history of the struggle of the Alas people against the Dutch colonial for students of SMA Negeri Semadam class XI IPS. To see the feasibility of the teaching material products made is as follows: the material expert assessment in the first stage validation obtained an average score of 3.90 converted based on a scale of 3 then it was declared sufficient, then in the second stage of validation the material expert had an average result of 4.09 converted based on a scale, namely 4 declared good. The assessment of media experts in the first stage of validation obtained an average score of 3.37 converted based on a scale, namely 3 was declared sufficient, then in the second stage of validation media experts had an average result of 4.62 converted based on a scale, namely 4 declared good. The trial of early stage small group students had an average result of 3.03 when converted on a scale of 3 was declared sufficient, then the advanced stage small group trial had an average result of 4.10 when converted on a scale of 4 was declared good, and the widely used trial had an average value of 4.10 and when converted based on a scale, namely 4 was declared good. From these results, this teaching material is declared suitable for use.